'Articles of Practical Banking Written by Practical Bankers': The Bankers' Magazine Reportage of the Great Irish Famine. (December 2016) - Curran, Declan
This article analyses the reportage of the banking publication Bankers' Magazine over the duration of the Great Irish Famine (1845–50). It explores attitudes to famine incidence and relief prevalent among Irish and British banking officials, as expounded in the trade publication representing their views. These professionals, employed in branch networks across both Irish and British society, were not political elites or ideologues, but rather saw themselves as 'practical bankers'. This analysis shows that the Bankers' Magazine reportage of the famine espoused, albeit in a measured rhetoric, the prevailing economic mindset based on self-reliance and the free market mechanism, while repeatedly acknowledging Irish famine-era suffering and reconciling itself to the expediency of 'unproductive' government-funded famine relief efforts. This analysis also shows the Bankers' Magazine 's famine reportage to have largely been subsumed by its campaign against the Bank Charter Act. More generally, the article argues that the Irish banking system offers a useful, though underutilised, lens through which to view famine-era socio-economic institutional workings and public opinion.